Resonant Scattering of Radiation Belt Electrons at Saturn by Ion Cyclotron Waves. Issue 3 (30th January 2023) - Cao, Xing; Lu, Peng; Ni, Binbin; Summers, Danny; Shprits, Yuri Y.; Long, Minyi; Wang, Xiaoyu
Abstract: By constructing an empirical model of the spectral and latitudinal distribution of ion cyclotron waves on the basis of Cassini datasets, we investigate the resonant interactions between ion cyclotron waves and radiation belt electrons at Saturn. Calculations based on quasi‐linear bounce‐averaged diffusion coefficients show that at Saturn ion cyclotron waves can efficiently pitch angle scatter >∼1 MeV to tens of MeV electrons into the loss cone thereby inducing precipitation loss, while the mixed and momentum scattering effects are typically negligible. The resultant electron loss timescales range from a few to tens of minutes, which in fact decrease significantly with increasing L ‐shell at L = 4–6. We also find that the kinetic effects introduced by pick‐up ring particles cause distinct changes in pitch angle scattering efficiency for lower energy electrons (<3 MeV at L = 5). Our results demonstrate that ion cyclotron waves play a significant role in the dynamics of Saturn's radiation belt electrons. Plain Language Summary: Ion cyclotron waves are a common electromagnetic wave mode in the planetary magnetospheres. At Saturn, ion cyclotron waves are usually observed with wave frequencies near the gyro‐frequency of water‐group ions (e.g., O +, OH +, and H2 O + ). They are known to be excited by a ring distribution of the pick‐up water‐group ions which are extracted from the extended neutral clouds. In this paper, we investigate the resonant interactions between ion cyclotron waves and radiation belt electrons at Saturn. By constructing an empirical model of the spectral and latitudinal distribution of ion cyclotron waves based on Cassini observations, we calculate the bounce‐averaged electron diffusion coefficients and resultant electron loss timescales. Our results suggest that Saturn's ion cyclotron waves can cause efficient precipitation loss of radiation belt electrons by scattering them into the loss cone. The corresponding loss timescales range from a few to tens of minutes, decreasing with increasing radial distance from Saturn. Our results confirm the important role of ion cyclotron waves in the dynamics of Saturnian radiation belt electrons. Key Points: The resonant interactions between ion cyclotron waves and radiation belt electrons at Saturn are investigated Ion cyclotron waves can efficiently pitch angle scatter >∼1 MeV to tens of MeV electrons into the loss cone for precipitation loss The resultant electron loss timescales range from a few to tens of minutes, which decrease significantly with increasing L ‐shell over L = 4–6